Identification of aflatoxigenic and non-aflatoxigenic strains of Aspergillus Section Flavi isolated from Portuguese almonds - Rodrigues, Paula (2011)
Aspergillus subgenus Circumdati section Flavi, also referred to as the A. flavus group, has attracted worldwide attention for its industrial use and toxigenic potential. Section Flavi is divided in two groups of species. One includes the aflatoxigenic species A. flavus, A. parasiticus and A. nomius, which cause serious problems in agricultural commodities, and the other one includes the non‐aflatoxigenic species A. oryzae, A. sojae and A. tamarii, traditionally used for production of fermented foods. Differentiating aflatoxigenic from non‐aflatoxigenic species and strains in food commodities is of major importance in food quality control. A polyphasic approach consisting of morphological, chemical and molecular characterization was applied to 31 isolates of Aspergillus Section Flavi originating from Portuguese almonds, with the aim of characterizing and identifying aflatoxigenic and non‐aflatoxigenic strains. On the basis of morphological characters, we found two distinct groups among the population under study: 58% were classified as A. parasiticus and the remaining 42% were classified as A. flavus. Chemical characterization involved the screening of the isolates for aflatoxins B (AFB) and G (AFG), and also for cyclopiazonic acid (CPA), by HPLC. All A. parasiticus isolates were strong AFB and AFG producers, but no CPA production was detected. The A. flavus isolates showed to be more diversified, with 77% being atoxigenic, whereas 15% produced CPA and low levels of AFB and 8% produced the 3 groups of mycotoxins. Molecularly, two genes of the aflatoxin biosynthetic pathway, aflD (=nor1) and aflQ (=ord1= ordA) were tested for presence and expression (by PCR and RT‐PCR, respectively). The presence of both genes did not correlate with aflatoxigenicity. aflD expression was not considered a good marker for differentiating aflatoxigenic from non‐aflatoxigenic isolates, but aflQ showed a good correlation between expression and aflatoxin‐production ability.